Pengaruh CAR dan NPL Terhadap ROA Pada PT Bank Permata Tbk Tahun 2011-2020 - Nadia Reynilda Aulia Putri; Hasbi Assidiki Mauluddi; Dadang Hermawan (Indonesian Journal of Economics and Management, 2021)
This study aims to determine whether there is an effect of Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) towards Return On Asset (ROA) at Permata Bank from period 2011 to 2020. The data used in this study uses secondary data from Quarterly Financial Statement Permata Bank period 2011–2020 published by Financial Services Authority of Indonesia (OJK). The sample used was as much as one company named Permata Bank as the object of research. The method used in this research is quantitative associative method. This study uses the IBM SPSS (Statistical Package for the Social Sciences) version 26 to process the data. The results of the research partially show that the Capital Adequacy Ratio (CAR) variable has positive and insignificant effect on Return On Asset (ROA), then Non Performing Loan (NPL) variable has a significant negative effect on Return On Asset (ROA). The result of the research simultaneously shows that Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) have an effect on Return On Asset (ROA).